Tweeting with Authority: Identifying Influential Participants in Agriculture-Related Water Quality Twitter Conversations - Ashlan E. Wickstrom; Annie R. Specht (Journal of Applied Communications, 2016)
In August 2014, Toledo, Ohio, experienced a dangerous algae bloom that led to a citywide water ban. News media coverage of the incident was widespread, as was social media conversation. Opinion leadership has been linked to news media agenda setting, and social media users are capable of generating considerable social influence within the sphere of their social networks. To better understand the dynamics of the conversation—especially as it pertained to agriculture—both during and after the water ban, the researchers used a social media analysis platform to identify high-influence Twitter users who participated in water-quality discussions about the Toledo water ban. Narrowing the search to agriculture-related discussion, the researchers revealed a dearth of agriculture-related content and also identified three categories of Twitter users in the conversation, including news sources, activists, and agriculture advocates. The researchers also found that Ohio users in post-ban discussions tended to be more influential than those who participated during the water ban. Identifying these users allows practitioners to monitor influential accounts for emerging issues and to engage with authoritative users in their geographic regions. The researchers also recommend that agriculture advocates exercise restraint in publicly speaking out about the industry’s involvement in environmental issues.
Keywords: Opinion Leadership; Social Influence; Social Media; Water Quality